Contamination of therapeutic human immunoglobulin preparations with apolipoprotein H (β2‐glycoprotein I). Issue 4 (24th November 2013) - Lackner, Friedrich; Beck, Gerhard; Eichmeir, Stephanie; Gemeiner, Manfred; Hummel, Karin; Pullirsch, Dieter; Razzazi‐Fazeli, Ebrahim; Seifner, Alexandra; Miller, Ingrid
<x xml:space="preserve">Abstract</x> Polyclonal immunoglobulin (Ig) concentrates are important biological medicinal products and the assurance of their quality and safety is crucial. In our present approach we used proteomic methods to check the purity of commercial Ig products of different origin. The experimental setup included nonreducing 2DE or DIGE combined with MALDI‐TOF and the thrombin generation assay, a routine safety test for pharmaceutical Ig preparations, and was complemented by a specific immunoassay. 2DE patterns displayed contaminations with trace amounts of human apolipoprotein H (Apo‐H), transferrin, albumin, and its fragments. In contrast to the latter, Apo‐H is a protein that is active in the coagulation cascade, and thus a potential involvement in thromboembolic events in vivo cannot be excluded. It was found by 2DE and MALDI‐TOF to be a contaminant of several Ig preparations. Spiking experiments of Ig preparations with pure Apo‐H demonstrated an Apo‐H concentration dependent increase in thrombin generation assay values. Traces of Apo‐H are possibly also contributing to unwanted side effects, as already known for factor XIa. The significance of Apo‐H contaminations for these side effects might be verified by detailed analyses of pharmacovigilance data.